What’s Trust Got to Do with It? Exploring Agricultural Science Podcast Producers’, Guests’, and Listeners’ Perceptions and Levels of Trust in Science - Jacqueline Aenlle; Jamie Loizzo; J.C. Bunch; Lisa K Lundy; Kevin M Folta (Journal of Applied Communications, 2023)
Little research to this point has examined food, agricultural, natural resource, and human science (FANRHS) podcast creation, the trustworthiness of the information presented, and the credibility of the individuals speaking on the podcast. The purpose of this study was to explore the level of trust in science of FANRHS podcast producers, guests, and listeners. The study followed an explanatory sequential mixed-method design beginning with an online survey instrument to measure trust in science and later, semi-structured interviews to further explore participants’ perceptions of trust and trust in science. Results showed participants had moderate to moderately high levels of trust in science. The study produced recommendations for podcast producers and guests regarding how to increase the credibility of their content and how to better foster science engagement. Future research should delineate trust based on various sub-topics within FANRHS and further explore specific communication tactics and framing strategies to create trusting relationships with podcast listeners.
Keywords: science communication; agricultural science; science engagement; outreach; podcast